Human–wildlife conflicts in Patagonia: ranchers’ perceptions of guanaco Lama guanicoe abundance - Flores, Celina; Lichtenstein, Gabriela; Schiavini, Adrián (Oryx, 2023)
Conflicts between people and wildlife have become widespread as people move to areas previously home to wildlife and as wild populations recover. In Patagonia, one of the main threats to guanaco Lama guanicoe conservation is the animosity of sheep ranchers towards the species. As key stakeholders in guanaco conservation we assessed ranchers’ perceptions regarding guanaco abundance in Isla Grande de Tierra del Fuego, Argentina. We contrasted these perceptions with estimated guanaco abundance and explored the socio-ecological factors influencing perceptions and how perceptions of overabundance are rooted in contextual factors rather than actual abundance. We performed semi-structured interviews with ranchers from Isla Grande and estimated guanaco abundance independently using density surface modelling. Ranchers were divided into three categories depending on their perception of guanaco abundance: ‘too many’, ‘many’ and ‘normal’. Those in the ‘many’ and ‘normal’ categories perceived guanaco abundance as being similar to actual abundance, whereas those in the category ‘too many' overestimated guanaco abundance. The perceived issues affecting livestock production varied between categories, although feral dogs emerged as the main problem. Negative perceptions of the guanaco stemmed from ranchers' beliefs that the species reduces forage availability for livestock, and from their disappointment about the government's handling of concerns regarding livestock production. Greater understanding and integration of the human dimension in conservation are needed to design more inclusive and resilient management plans.